Chronic Traumatic Encephalopathy in Sports Practice: A Literature Review - Abad, Luiz Henrique Salamoni; Lessa, Ruan Teixeira; Mesquita, Francielle Bianca Moreira de; Silva, Vitória Leite; Cesar, Marcelo Ribeiro; Ferreira, Tayná Beato; Costa, Ana Julia Rodrigues da; Buzan, Thales Nascimento; Mendes, Nathália Barbosa do Espírito Santo (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Chronic traumatic encephalopathy (CTE) is a neurodegenerative syndrome caused by repetitive and cumulative head trauma. Due to the widespread practice of contact and collision sports, a discussion of the long-term repercussions of repeated head trauma is imperative. The present literature review, performed through the SciELO, PUBMED, and BVS-Bireme databases, includes studies conducted since the year 2000, which established the relationship between CTE and the practice of sports. The diagnosis of CTE was notably present in individuals practicing sports that involve repeated traumatic brain injuries. The noticeable changes triggered by CTE include a series of clinical and neuropathological manifestations that can help in the differentiation from other tauopathies.
Keywords: traumatic brain injuries; brain concussion; chronic traumatic encephalopathy; tauopathies